Pengaruh Indikator Sektor Keuangan (DPK, Kredit dan Investasi) terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Selatan - Saudah, Siti; Nuryadin , Muhammad Rusmin (PPJP ULM, 2022)
This research was conducted to analyze the effect of financial sector indicators on economic growth in the South Kalimantan Province. The needles used are third-party funds, credit, and investment. Descriptive quantitative is the approach used in this study. By obtaining data sources in the form of time series data originating from the Central Statistics Agency and Bank Indonesia from 2006-to 2018, the data is processed multiple linear regression method After processsing and analyzing the data, in this study the result were obtained : (1) the variable third party funds on economic growth showed positive and significant results, then credit and investment variables showed different result with a negative but significant on economic growth (2) The variable with the biggest impact is the third party funds variable with a coefficient 0,336111